Izin Industri, Bagaimana Implementasinya? - Sri Syabanita Elida; Desvira Zain; Oryza Arisandra (FORBISWIRA FORUM BISNIS DAN KEWIRAUSAHAAN - SINTA 4, 2021)
This research aims to determine the implementation of industrial licensing at one of the offices in the city of Pontianak, namely: Trade Micro Business Cooperative (DKUMP). The methodology used in this research is quantitative research methodology, while the approach used is a descriptive approach. The data collection technique in this research is a questionnaire and distributed to 46 respondents. Based on the results of data analysis, it can be seen that the index value of the Industrial Licensing Implementation of the DKUMP Pontianak City is categorized as high.